Kebijakan dan Tantangan Penegakan Etika Profesi Guru pada Era Digital - Jumhuriyatus Sa’diyah; Ma’mun Hanif; Nabila Imtiyas Ramadhani; Heida Rahma Eksanti; Diva Nadiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A key factor in the quality of national education is teacher ethics. In the digital era, the application of professional ethics by educators faces challenges, particularly related to the inappropriate use of social media. This study aims to analyze government regulations on teacher ethics through Law Number 14 of 2005 and the Indonesian Teacher Code of Ethics, as well as to identify the obstacles and challenges of its implementation. The method used is a literature review by examining articles from accredited journals and government policy documents from 2020 to 2025. The results show that many teachers do not yet understand the code of ethics, supervision remains weak, and there is a lack of specific regulations to measure teacher conduct in the digital world, despite the existence of adequate ethical rules.